Selling Solutions Isn't Enough - Ettenson, Richard; Grove, Hannah; Knowles, Jonathan; Sellers, Kevin (MIT Sloan Management Review, 2018)
Rather than trying to sell standardized products or services to the biggest possible set of buyers, B2B companies need to develop ways to help specific customers achieve better outcomes. Instead of describing their solutions, companies first need to understand customers' specific challenges, objectives, operating practices, and competitive environment, then create offerings to deliver value within a customer's specific business context and culture.